Inventário dos Drosofilídeos (Diptera) associados a frutos, na Floresta Nacional de Caxiuanã, Melgaço, Pará, Brasil - PRAXEDES, Catarina de Lurdes Bezerra (Universidade Federal do Pará, 2013)
The objective of this study was to describe the diversity of frugivorous Drosophilidae (Diptera) in Caxiuanã National Forest, Melgaço, Pará, Brazil, utilizing a structured protocol. Two collecting expeditions were carried out betvveen 2003 and 2004. Traps baited with banana were distributed along 12 one km transects in each of 6 arcas separating the parallel streams flowing from the north into Caxiuanã bay in the "Ferreira Pena" Scientific Station in Caxiuanã National Forest. A total of 4,320 individuais were collected, belonging to 36 taxons in two genera Drosophila (subgenus Sophophora and Drosophila) and Neotanygastrella. The dominant species collected was D. willistoni, comprising 33.96% of ali individuais, followed by D. paulistorunt (21.94%), D. sturtevanti (18.73%), D. tropicahs (11.39%) and D. equinoxialis (6.37%) Five cosmopolitan species of melanogaster group occur in Caxiuanã, but the frequency of the group was only 1.75%. Species accumulation curves, generated by EstimateS, approached an asymptote with 315 samples, resulting in estimates from 40 to 53 total species. The Chao2 estimator produced curves that appmached stabilization with an estimate of 50 species. Analyses of the incidence and abundance matrix demonstrated that the collecting localities were similar, sharing from 40% to 66% in composition (Jaccard), with similar distributions of abundance (Morisita values between 85% and 100%). The percentage completeness of the inventory (79%) indicates that only 83 additional samples are necessary (21% increase in sampling effort, without addition singletons) in order to assess the total diversity of frugivorous Drosophilidae. These results demonstrate the efficiency of the methodology used for estimating the diversity of frugivorous drosophilids in Caxiuanã. Of the 23 subgenus Sophophora species collected, 4 were new records for Brazil (D. dacunhai, D. milleri, D. sahans, and D. septentriosaltans) and 8 were new records for Brazilian Arnazonia (D. austrosahans, D. dacunhai, D. magalhaesi, D. milleri, D. neocordata, D. neoelhptica, D. saltans, and D. septentriosahans).